Adolescents' Misuse of Over-The-Counter Medications: The Need for Pharmacist-led Intervention - Olufunmilola Abraham; Jessica Chmielinski (University of Minnesota Libraries Publishing, 2018)
Adolescents' misuse of over-the-counter (OTC) medications is a growing patient safety concern, resulting in an alarming number of poisonings and emergency department visits. OTC medications are easily accessible and adolescents often have the misconception that these medications are safe, even at higher than recommended doses. Dextromethorphan and acetaminophen are the most common and frequently misused OTC medications among adolescents, with significantly dangerous health risks if used improperly. Pharmacists are critical to the provision of education on safe OTC medication use for adolescents and their family caregivers by leading and implementing relevant community-based interventions. Ideal channels in which to do this in the community are pharmacies and schools. It is challenging to gain the attention of adolescents and to engage them; methods that include innovative measures and initiatives may be the solution. Research is needed to determine how pharmacists can improve adolescents' knowledge and safe use of OTC medications. Pharmacists must be supported through training and acquisition of expertise specific to adolescent engagement and education. The development of pharmacist-led educational interventions that are tailored for adolescents that address their limited OTC medication knowledge and raise awareness of safety risks associated with misuse is crucial to preventing and reducing this patient safety problem in the community. Conflict of Interest: None   Article Type: Commentary